2020
DOI: 10.19080/oajnn.2020.14.555882
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Stroke with a Plant-Based Diete

Abstract: Current known modifiable risk factors for stroke together account for more than 90% of population attributable risk. A plant-based diet has been shown to reduce the risk of stroke by 28-48%, and to significantly reduce the biggest risk factors -hypertension, coronary heart disease, and type 2 diabetes. Vegetarians have been found to have a 34-44% lower risk of developing hypertension, and a 40% reduced risk of ischemic heart disease. Vegans have a 78% lower risk of type 2 diabetes and a 75% reduced risk of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Research has suggested that a well-planned plant-based diet is equally as successful at lowering cholesterol as statin medications and a highly advantageous alternative to other treatment strategies [ 102 ]. At the same time, it has the distinct benefits of having no side effects or contraindications, is affordable, and has high patient compliance [ 103 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Research has suggested that a well-planned plant-based diet is equally as successful at lowering cholesterol as statin medications and a highly advantageous alternative to other treatment strategies [ 102 ]. At the same time, it has the distinct benefits of having no side effects or contraindications, is affordable, and has high patient compliance [ 103 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…For instance, the plant-based diet is as efficacious as Lovastatin and is more efficacious than Metformin in treating type 2 diabetes [80,41]. It also reduces the risk of several other pathologies such as coronary artery disease [80] stroke [81] osteoarthritis [82] prostate and colon cancer, [83,84] diverticular disease [85] ulcerative colitis [86]. Crohn's disease [87].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Vegetarians have been found to have a 34-44% lower risk of developing hypertension, and a 40% reduced risk of ischemic heart disease. Vegans have a 78% lower risk of type 2 diabetes and a 75% reduced risk of hypertension compared to meat eaters with an otherwise healthy lifestyle [84]. Thus a plant-based diet is both a valuable prophylaxis and treatment for ED and for several other pathologies.…”
Section: Clinical Considerationsmentioning
confidence: 99%